Manage Sistem Operasi Digitalisasi SPBU Pertamina Daerah Operasional PT. Telkom Indonesia Regional IV Witel Semarang - Ahmad - Fauzi; Akhmad Fathurohman; Timotus Nandra Pratyaksa (JURNAL KOMPUTER DAN TEKNOLOGI INFORMASI, 2023)
Practical Work carried out at PT. Telkom Indonesia Division of SPBU Regional IV Witel Semarang which is located on Jl. Singotoro No.20, Jomblang, Candisari, Semarang City, Central Java 50256. PT. Telkom Access, which is a subsidiary of PT. Telekomunikasi Indonesia Tbk. which is engaged in the construction and management of network infrastructure services. And the SPBU (General Fuel Filling Station) digitization project, Telkom and Pertamina are collaborating to monitor the distribution of fuel (fuel oil) throughout Indonesia. This practical work report discusses the Manage Operation of Digitizing Pertamina Gas Stations Operational Area PT.Telkom Indonesia Regional IV Witel Semarang, using the Single Dashboard Monitoring System (SDMS) web-based system in the https://sdms.spbu.id/ domain in the system understand the procedures and processes for monitoring Public Fuel Filling Stations (SPBU) in the Region IV Witel Semarang Region that use an EDC (Electronic Data Capture) machine connected to a computer network Manage Operations Digitalization is an activity formonitoring or processing a data by utilizing digitization.Starting from 30 January 2023 to 03 March 2023.